Kewenangan Paralegal Dalam Pemberian Bantuan Hukum : Perspektif Putusan Mahkamah Agung No. 22/P/HUM/2018 - Permana, Bayu; Arsha Putra, I Putu Rasmadi (Kertha Wicara : Journal Ilmu Hukum, 2020)
This research aims to provide a clear definition of the development of the Paralegal in Indonesia, and also to provide an explanation of the authority of the Paralegal after the ruling of the Supreme Court of the Republic of Indonesia Number 22 / P / HUM / 2018. The reserach method used in this journal is a normative judicial research method by collecting primary and secondary legal materials. The approach used is the statute approach which describes the existence of a conflict of norms which is then linked to a conceptual approach, as well as in analyzing legal materials using descriptive techniques and using qualitative analysis techniques with narrative writing which then contains conclusions. The results showed that the development of Paralegals in Indonesia could initially be said to be known around the 1970s. Through Decision Number 22 / P / HUM / 2018, which resulted in Articles 11 and 12 of the Minister of Law and Human Rights Regulation No. 1 of 2018 concerning Paralegal in Providing Legal Aid revoked or abolished so that the authority of the Paralegal can no longer stand alone in conducting legal proceedings in court. It is recommended to the Minister of Law and Human Rights of Republic Indonesia to make a clearer regulation regarding the definition of Paralegal so as to provide clarity about Paralegal because until now there has not been any clarity about the definition of Paralegal.   Keywords : Paralegal, communities, welfare